2015
DOI: 10.1089/vim.2014.0123
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Blood Levels Distinguish Between Influenza A (H1N1)pdm09 Virus Sepsis and Sepsis due to Other Forms of Community-Acquired Pneumonia

Abstract: There is a strong interest in finding adequate biomarkers to aid in the diagnosis and prognosis of influenza A (H1N1)pdm09 virus infection. In this study, serum levels of inflammatory cytokines and laboratory markers were evaluated to assess their usefulness as biomarkers of influenza A (H1N1)pdm09 and their association with fatal cases. Serum samples of consecutive patients with a clinical presentation suggestive of influenza A (H1N1)pdm09 and progression to sepsis were evaluated. Serum inflammatory cytokines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Our data support this finding, in that, among the proven cases of influenza virus, 49.2% had CAP, 25.8% had SAS with acute pneumonia, and up to 50% of patients had signs of respiratory distress. Neurological, hemodynamic, and cardiovascular complications have also previously been described in the context of severe infections that have been complicated by influenza [ 27 , 28 ]; in the present study, 12% of patients with influenza had hemodynamic disorders and 6% had neurological disorders. Some of the sepsis-like events that were observed in the group with hemodynamic failure could be related to frequent bacterial superinfection, which has been described in such patients [ 29 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our data support this finding, in that, among the proven cases of influenza virus, 49.2% had CAP, 25.8% had SAS with acute pneumonia, and up to 50% of patients had signs of respiratory distress. Neurological, hemodynamic, and cardiovascular complications have also previously been described in the context of severe infections that have been complicated by influenza [ 27 , 28 ]; in the present study, 12% of patients with influenza had hemodynamic disorders and 6% had neurological disorders. Some of the sepsis-like events that were observed in the group with hemodynamic failure could be related to frequent bacterial superinfection, which has been described in such patients [ 29 ].…”
Section: Discussionsupporting
confidence: 74%
“…Respiratory distress was the main symptom, with up to 45% of patients exhibiting signs of clinically significant respiratory distress. It has previously been reported that 16% of cases of seasonal influenza occur in clinical pulmonary patients [ 24 ], 36% may develop acute pneumonia [ 24 , 25 ] and 20% may develop respiratory failure [ 25 28 ]. Our data support this finding, in that, among the proven cases of influenza virus, 49.2% had CAP, 25.8% had SAS with acute pneumonia, and up to 50% of patients had signs of respiratory distress.…”
Section: Discussionmentioning
confidence: 99%
“…The PLR has been reported to predict the severity and prognosis of pneumonia. 10 Our research also shows that the PLR was a main factor influencing the T cell subsets; fighting SARS-CoV-2 exhausts the T cells, 11 and monitoring changes in platelet counts and the PLR can help reveal the body’s immune function status to a certain extent. In the current epidemic period, isolated observation areas and fever clinics are usually unable to test CD3+, CD4+ and CD8+ T cell counts.…”
Section: Discussionmentioning
confidence: 64%
“…The activated type I receptor can activate Smad proteins that regulate transcription [ 14 ]. A previous study has shown that the blood level of TGF-β could distinguish between H1N1 virus sepsis and sepsis due to other forms of community-acquired pneumonia [ 15 ]. In addition, levosimendan upregulated TGF-β and Smad signaling in the aorta in the early stage of sepsis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%